Chronic alcohol-induced long-lasting working memory deficits are associated with altered histone H3K9 dimethylation in the prefrontal cortex - De Clerck, Mael; Manguin, Martin; Henkous, Nadia; d’Almeida, Marion N.; Beracochea, Daniel; Mons, Nicole (Frontiers in Behavioral Neuroscience, 2024)
Introduction Epigenetic modifications have emerged as key contributors to the enduring behavioral, molecular and epigenetic neuroadaptations during withdrawal from chronic alcohol exposure. The present study investigated the long-term consequences of chronic alcohol exposure on spatial working memory (WM) and associated changes of transcriptionally repressive histone H3 lysine 9 dimethylation (H3K9me2) in the prefrontal cortex (PFC). Methods Male C57BL/6 mice were allowed free access to either 12% (v/v) ethanol for 5 months followed by a 3-week abstinence period or water. Spatial WM was assessed through the spontaneous alternation T-maze test. Alcoholic and water mice received daily injections of GABAB agonist baclofen or saline during alcohol fading and early withdrawal. Global levels of histone modifications were determined by immunohistochemistry. Results Withdrawal mice displayed WM impairments along with reduced prefrontal H3K9me2 levels, compared to water-drinking mice. The withdrawal-induced decrease of H3K9me2 occurred concomitantly with increased level of permissive H3K9 acetylation (H3K9ac) in the PFC. Baclofen treatment rescued withdrawal-related WM deficits and fully restored prefrontal H3K9me2 and H3K9ac. Alcohol withdrawal induced brain region-specific changes of H3K9me2 and H3K9ac after testing, with significant decreases of both histone marks in the dorsal hippocampus and no changes in the amygdala and dorsal striatum. Furthermore, the magnitude of H3K9me2 in the PFC, but not the hippocampus, significantly and positively correlated with individual WM performances. No correlation was observed between H3K9ac and behavioral performance. Results also indicate that pre-testing intraperitoneal injection of UNC0642, a selective inhibitor of histone methyltransferase G9a responsible for H3K9me2, led to WM impairments in water-drinking and withdrawal-baclofen mice. Collectively, our results demonstrate that alcohol withdrawal induced brain-region specific alterations of H3K9me2 and H3K9ac, an effect that persisted for at least three weeks after cessation of chronic alcohol intake. Conclusion The findings suggest a role for long-lasting decreased H3K9me2 specifically in the PFC in the persistent WM impairments related to alcohol withdrawal.